Threadbare Morality and The New World in Jane Austen’s Pride and Prejudice - Ashfaq, Samina; Jamal Khattak, Nasir (The Journal of Humanities & Social Sciences, 2023)
Jane Austen’s attitude towards morality has always been a debatable topic for those who consider morality as an integral part of religion. Though the daughter of a clergyman, she never discusses religion in her novels which is why she remains popular to this day. Austen, a keen observer of her society, can see that times change with new ideologies, inventions and contact with others at universal level because of modern means of communications. She knows that acceptance and respect for the opinions of others can lead to greater understanding and world peace. Her art of creating a microcosm which she calls “little bit (two inches wide) of ivory” 1 conveys the message through the stories of few families. This paper is an attempt to search how she tries to harmonize the characters of her novel belonging to different classes and social groups, by making them realize that if they keep on sticking to their old worn-out beliefs, they will never be able to bridge the gap with the others and taste the fruits of wholesome relationships.